An Ethical Exploration of Barriers to Research on Controlled Drugs. Issue 4 (2nd April 2016) - Andreae, Michael H.; Rhodes, Evelyn; Bourgoise, Tyler; Carter, George M.; White, Robert S.; Indyk, Debbie; Sacks, Henry; Rhodes, Rosamond
Abstract : We examine the ethical, social, and regulatory barriers that may hinder research on therapeutic potential of certain controversial controlled substances like marijuana, heroin, or ketamine. Hazards for individuals and society and potential adverse effects on communities may be good reasons for limiting access and justify careful monitoring of these substances. Overly strict regulations, fear of legal consequences, stigma associated with abuse and populations using illicit drugs, and lack of funding may, however, limit research on their considerable therapeutic potential. We review the surprisingly sparse literature and address the particular ethical concerns pertinent to research with illicit and addictive substances, such as undue inducement, informed consent, therapeutic misconception, and risk to participants, researchers, and institutions. We consider the perspectives of key research stakeholders and explore whether they may be infected with bias. We conclude by proposing an empirical research agenda to provide an evidentiary basis for ethical reasoning.